To solve the given problem using mathematical induction, we will proceed as follows:
The statement to prove:
For all natural numbers n,
∑r=1n(2+3(r−1))=2n(4+3(n−1)).
Step 1: Base Case (n=1)
Substitute n=1 into both sides of the equation:
-
Left-hand side (LHS):
∑r=11(2+3(r−1))=2+3(1−1)=2+0=2.
-
Right-hand side (RHS):
21(4+3(1−1))=21⋅(4+0)=21⋅4=2.
Since LHS=RHS, the base case holds true.
Step 2: Inductive Hypothesis
Assume the statement is true for n=k:
∑r=1k(2+3(r−1))=2k(4+3(k−1)).
We aim to prove it for n=k+1, i.e.,
∑r=1k+1(2+3(r−1))=2k+1(4+3(k+1−1)).
Step 3: Inductive Step
Using the assumption for n=k, we have:
∑r=1k+1(2+3(r−1))=∑r=1k(2+3(r−1))+(2+3(k)).
Substitute the inductive hypothesis:
∑r=1k+1(2+3(r−1))=2k(4+3(k−1))+(2+3k).
Simplify the RHS:
-
Expand the term 2k(4+3(k−1)):
2k(4+3(k−1))=2k(4+3k−3)=2k(3k+1).
-
Add 2+3k to it:
2k(3k+1)+2+3k.
-
Rewrite 2k(3k+1) in expanded form:
23k2+2k.
Thus, the total becomes:
23k2+2k+2+3k.
Simplify by combining like terms:
23k2+(2k+3k)+2=23k2+27k+2.
Factor out 21:
21(3k2+7k+4).
Step 4: Simplify for k+1
Expand the RHS for n=k+1:
2k+1(4+3(k+1−1))=2k+1(4+3k).
Simplify 4+3k:
2k+1⋅(3k+4).
Expand:
21((k+1)(3k+4)).
Multiply out (k+1)(3k+4):
(k+1)(3k+4)=3k2+4k+3k+4=3k2+7k+4.
Thus, the RHS becomes:
21(3k2+7k+4).
Conclusion
The LHS for n=k+1 matches the RHS:
21(3k2+7k+4).
By induction, the statement is true for all n.
Let me know if you'd like further clarification or have questions about any step! Here are related questions for practice:
- What is the general approach for mathematical induction?
- How do you simplify summations in problems like this?
- Why is the base case essential in induction proofs?
- Can you prove a similar formula for arithmetic series by induction?
- How would you test whether the formula holds numerically for n=5?
Tip: Always verify your work in the inductive step by expanding carefully!